2016
DOI: 10.1353/csd.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Career Aspirations and the First Generation Student: Unraveling the Layers With Social Cognitive Career Theory

Abstract: Undergraduate students who are the first in their immediate family to go to college represent a unique population on campus deserving special attention to their educational and career development needs. We explored career development characteristics of first-generation college students and compared them to those who are not first-generation, using Lent, Brown, and Hackett’s (1994) social cognitive career theory as a theoretical base. Findings indicated significant differences between the 2 groups, and the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 34 publications
2
84
2
1
Order By: Relevance
“…En la actualidad, existe un gran cuerpo de investigaciones en torno a los modelos derivados de esta teoría (e.g. Atadero, Rambo-Hernandez & Balgopal, 2015;Bocanegra, Gubi & Cappaert, 2016;Chang & Edwards, 2015;Kaminsky & Behrend, 2015;Lee, Flores, Navarro & Kanagui-Muñoz, 2015;Lent, et al, 2015;Raque-Bogdan & Lucas, 2016;Roche, Daskalova & Brown, Efectos Efecto Indirecto Efecto Total 2016; Thompson, Dahling, Chin & Melloy, 2016;Thungjaroenkul, Cummings & Tate, 2016). La mayoría de estos estudios se han realizado en poblaciones estadounidenses, con estudiantes universitarios y pocos de ellos contemplan la influencia de las cuatro fuentes de información que dan origen a las creencias de autoeficacia.…”
Section: Conclusionesunclassified
“…En la actualidad, existe un gran cuerpo de investigaciones en torno a los modelos derivados de esta teoría (e.g. Atadero, Rambo-Hernandez & Balgopal, 2015;Bocanegra, Gubi & Cappaert, 2016;Chang & Edwards, 2015;Kaminsky & Behrend, 2015;Lee, Flores, Navarro & Kanagui-Muñoz, 2015;Lent, et al, 2015;Raque-Bogdan & Lucas, 2016;Roche, Daskalova & Brown, Efectos Efecto Indirecto Efecto Total 2016; Thompson, Dahling, Chin & Melloy, 2016;Thungjaroenkul, Cummings & Tate, 2016). La mayoría de estos estudios se han realizado en poblaciones estadounidenses, con estudiantes universitarios y pocos de ellos contemplan la influencia de las cuatro fuentes de información que dan origen a las creencias de autoeficacia.…”
Section: Conclusionesunclassified
“…he Bureau of Labor Statistics (2019) reported that the median weekly salary was $1,340 for those with a bachelor's degree and $746 for those with only a high school diploma. These statistics speak to the societal value of completing a college education, an endeavor that is particularly challenging for first-generation college students (FGCS), who often come from lower socioeconomic status (SES) backgrounds, have lower college retention and graduation rates, and often take significantly longer to complete a degree in comparison with their continuing-generation peers (Engle & Tinto, 2008;Martin, 2017;Raque-Bogdan & Lucas, 2016;Tate et al, 2015;Ward et al, 2012). Even when FGCS persist to a doctoral program, they tend to produce less scholarly work early in their programs (Roksa et al, 2018).…”
mentioning
confidence: 99%
“…First-generation will refer to an undergraduate college student for whom neither parent(s) and/or legal guardian has received a degree from a post-secondary institution (Billson & Terry, 1982;Engle, 2007;Gibbons & Shoffner, 2004;Pascarella, et al, 2004;Raque-Bogdan & Lucas, 2016). It is important to note there are a range of definitions for FG students including, those whose parent(s) and/or legal guardian have never enrolled in or attended formal education beyond high school to those whose parent(s) and/or legal guardian may have enrolled and attended college but did not complete a degree (Means, et al, 2016;Raque-Bogdan & Lucas, 2016). This study sought to capture a wide range of FG participant perspectives, therefore included participants for whom neither parent(s) and/or legal guardian completed a post-secondary degree.…”
Section: First-generation (Fg)mentioning
confidence: 99%
“…Continuing generation refers to students for whom at least one parent enrolled in and successfully completed a college degree (Billson & Terry, 1982;Choy, 2001;Lohfink & Paulsen, 2005;Orbe, 2007;Pascarella, et al, 2004;Raque-Bogdan & Lucas, 2016;Saenz, et al, 2007).…”
Section: Continuing Generation (Cg)mentioning
confidence: 99%